Pengaruh Kualitas Produk dan Pelayanan Terhadap Loyalitas Pelanggan SFA Steak & Resto Gentan Mangesti - Nafisah Azzahro; Muhammad Syihabuddin (PT. Karya Inovatif Nusantara, 2025)
This study aims to examine the influence of product quality and service quality on customer loyalty at SFA Steak & Resto Gentan Mangesti, a growing casual dining restaurant. As competition in the culinary industry intensifies, restaurants are required to maintain consistent product quality while enhancing service performance to retain loyal customers. A quantitative associative research design was employed, involving 128 respondents selected through purposive sampling. The data analysis included validity and reliability testing, classical assumption tests, and multiple linear regression.The findings reveal that product quality has a positive and significant effect on customer loyalty, whereas service quality does not exhibit a significant direct influence. Nevertheless, both variables jointly contribute significantly to customer loyalty, with the model explaining 22.8 percent of the variance. These results indicate that customers in casual dining settings place stronger emphasis on functional aspects such as taste, consistency, and portion suitability when forming loyalty, while service quality is perceived as a complementary factor enhancing overall perceived value. Theoretically, the study reinforces the view that product quality serves as the foundation for long-term customer loyalty. Practically, the findings suggest the need for stronger product quality control and gradual improvement in service delivery. Future studies are encouraged to incorporate additional variables such as customer satisfaction, pricing, and restaurant atmosphere to broaden analytical insights.